Rural tourism in Malaysia - Jaafar, Mastura; Marzuki, Azizan; Abdullah, Shardy (Penerbit Universiti Sains Malaysia, 2019)
Rural tourism provides opportunities for travellers to experience rural attractions and getting familiar with the culture and heritage. It is known to stimulate rural economy through job creation, farm support, nature conservation, rural supplies and services, landscape and nature conservation, rural arts and crafts, and enrichment of local heritage. The development will profit the local community through tourism products ranging from ecotourism to cultural tourism. With rich and melting pot of multicultural and biodiversity, Malaysia has great potential in rural tourism. Both Peninsular Malaysia and East Malaysia have the best ecotourism destinations in the region. Malaysia is blessed to have the UNESCO branded rural destinations such as Kinabalu Park, Gunung Mulu National Park and Archaeological Heritage of the Lenggong Valley. The rural tourism concept in Malaysia has been integrated with other tourism concepts such as sustainable tourism, indigenous tourism, ethnic tourism, agrotourism, ecotourism, farm tourism, cultural tourism and heritage tourism. This integrated concept has been explored in a few case studies involving archaeological, ecotourism, mangrove and highland tourism of rural destinations. These rural destinations offer great potentials in providing the ‘truly Malaysia’ experiences; however, it is yet to be fully capitalized. Managing rural tourism development is very challenging due to its limited resources and infrastructure; thus identification on how the destination is presented, managed and promoted are the major focus of this book. Therefore, these interesting case studies are hoped to enlighten the development of the selected rural tourism destinations in Malaysia.